2011
DOI: 10.1002/hipo.20933
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for area CA1 as a match/mismatch detector: A high‐resolution fMRI study of the human hippocampus

Abstract: Summary The hippocampus is proposed to switch between memory encoding and retrieval by continually computing the overlap between what is expected and what is encountered. Central to this hypothesis is that area CA1 performs this calculation. However, empirical evidence for this is lacking. To test the theoretical role of area CA1 in match/mismatch detection, we had subjects study complex stimuli and then, during high-resolution fMRI scanning, make memory judgments about probes that either matched or mismatched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
203
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(228 citation statements)
references
References 44 publications
24
203
1
Order By: Relevance
“…There were two main findings. First, activity during the decision probe was greater in CA 1 and PRc when the participant correctly recalled the learned associate and the recognition probe differed from (mismatched) this retrieved memory, a finding consistent with the hypothesis that CA 1 acts as a comparator, differentiating between perceptual inputs that are mnemonically unexpected vs. expected (e.g., Lisman and Grace 2005; for related hr-fMRI data, see Duncan et al 2011). In this framework, mismatches may constitute associative "prediction errors" between expected and actual events, analogous to those described in models of reinforcement learning (Rescorla and Wagner 1972).…”
Section: Retrieval and Mismatch Detection In Human Mtlsupporting
confidence: 68%
See 2 more Smart Citations
“…There were two main findings. First, activity during the decision probe was greater in CA 1 and PRc when the participant correctly recalled the learned associate and the recognition probe differed from (mismatched) this retrieved memory, a finding consistent with the hypothesis that CA 1 acts as a comparator, differentiating between perceptual inputs that are mnemonically unexpected vs. expected (e.g., Lisman and Grace 2005; for related hr-fMRI data, see Duncan et al 2011). In this framework, mismatches may constitute associative "prediction errors" between expected and actual events, analogous to those described in models of reinforcement learning (Rescorla and Wagner 1972).…”
Section: Retrieval and Mismatch Detection In Human Mtlsupporting
confidence: 68%
“…Similarly, Duncan et al (2009) observed greater hippocampal activity when the probe matched an imagined display, but greater activation on mismatch trials when the probe contained unexpected perceptual novelty. The first pattern was interpreted as a goal-modulated match signal, and the second as an automatic mismatch signal (for related CA 1 data, see Duncan et al 2011). By contrast, Dudukovic et al (2011) proposed that match enhancement occurs when a previously encountered stimulus (e.g., a decision probe) triggers the retrieval of other event details that co-occurred with the stimulus's previous encounter.…”
Section: Retrieval and Mismatch Detection In Human Mtlmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find a significant link between the state of CA1 during encoding and memory, although there were theoretical reasons to expect CA1 modulation, including that CA1 activity is influenced by goal states during memory retrieval (28). Future studies will be needed to clarify how and when attention modulates mnemonic processes in different subfields.…”
Section: Discussionmentioning
confidence: 63%
“…Another candidate for the attentional modulation of memory is CA1. Activity in the CA1 subfield is modulated by goal states during memory retrieval (28), and this region serves as a "comparator" of expectations-which may be induced by attentional cues-and percepts (29,30).…”
Section: Significancementioning
confidence: 99%